2007
DOI: 10.1158/1078-0432.ccr-06-1404
|View full text |Cite
|
Sign up to set email alerts
|

α1-Antitrypsin Precursor in Gastric Juice Is a Novel Biomarker for Gastric Cancer and Ulcer

Abstract: Purpose: To search for novel disease-specific markers in gastric juice by investigating the protein concentrations and components in gastric juice from patients with various gastroduodenal diseases. Experimental Design: Protein concentrations and pH values in fasting gastric juice were examined in 120 healthy subjects and 39 gastric ulcer, 38 duodenal ulcer, and 31 gastric cancer patients. The protein components in gastric juice were studied by two-dimensional PAGE and mass spectrometric analysis. Results: Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 26 publications
5
47
1
Order By: Relevance
“…Gastric cancer patients had higher frequencies of α1-antitrypsin and albumin peaks and lower frequencies of leucine zipper protein and pepsinogen peaks than healthy subjects (12). Another our study (11) showed a prominent band of α1-antitrypsin in the two-dimensional gastric juice electrophoresis image of gastric juice samples from gastric cancer patients. However, the α1-antitrypsin band seemed not to be cancer specific because a small α1-antitrypsin band was also identified in the gastric juices from 42%, 6%, and 6% of gastric ulcer patients, duodenal ulcer patients, and healthy subjects, respectively.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Gastric cancer patients had higher frequencies of α1-antitrypsin and albumin peaks and lower frequencies of leucine zipper protein and pepsinogen peaks than healthy subjects (12). Another our study (11) showed a prominent band of α1-antitrypsin in the two-dimensional gastric juice electrophoresis image of gastric juice samples from gastric cancer patients. However, the α1-antitrypsin band seemed not to be cancer specific because a small α1-antitrypsin band was also identified in the gastric juices from 42%, 6%, and 6% of gastric ulcer patients, duodenal ulcer patients, and healthy subjects, respectively.…”
Section: Discussionsupporting
confidence: 50%
“…In clinical practice, it might be difficult to differentiate gastric cancer from gastric ulcer in some patients with mild elevation of gastric juice α1-antitrypsin concentrations. Our previous study has shown that leukocyte elastase inhibitor, desmoglein-1 precursor, and immunoglobulin κ chain C region were other potential biomarkers for gastric cancer in gastric juices (11). A scoring system using the combination of different measurements, such as the gastric juice pH, protein concentration, α1-antitrypsin, and other biomarker levels, could potentially give more accurate results than a single gastric juice biomarker for the discrimination of gastric cancer and merits further investigations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteomic analysis with 2-DE can simultaneously detect changes of multiple proteins in plasma often detected differentially expressed proteins are common abundant plasma proteins and their diagnostic value may be limited. Twodimensional electrophoresis (2-DE) has been used for the discovery of circulating auto-antibodies in cancer patients and annexins I and II were reported as specific antigens in sera from patients with lung [Nolen and Lokshin, 2013]; b-2 microglobulin [Yang et al, 2009] apolipoprotein [Podzielinski et al, 2013]; gene-expression in HE4 [Ferraro et al, 2013 [Du et al, 2013]; AGR2 [Li et al, 2015c]; ubiquitin ligase [Goka and Lippman, 2015]; ferritin light chain [Jezequel et al, 2012] Gastric cancer a1-antitrypsin precursor [Hsu et al, 2007]; pepsinogen C [Terasawa et al, 2014]; Cathepsin B [Ebert et al, 2005]; galectin-1/-3 [Thijssen et al, 2015]; miR-214 [Zhang et al, 2015b]; angiopoietinlike protein 2 [Yoshinaga et al, 2015]; MOR1 [Yao et al, 2015]; circular RNA [Li et al, 2015a] Liver cancer Galectin-1/-3 [Thijssen et al, 2015]; CHI3L1/MASP2 [Ding et al, 2014]; Sall4, Glypican-3, dickkopf-1 and talin-1 [Chatterjee and Mitra, 2015] …”
Section: Plasma Proteomics In Tumorsmentioning
confidence: 99%
“…Several reports have corroborated elevated levels of AAT in gastric juice in patients with gastric cancer compared with healthy controls. (Hsu et al 2007;Lee et al 2004) …”
Section: Stomachmentioning
confidence: 99%